Two Unusual Presentations of Presacral Schwannoma; A Case Series. (2019) - Kalagi, Dana; Bakir, Mohammed; Alfarra, Mohammad; Aborayya, Alaa; Anwar, Ihab
Highlights: Schwannomas are benign tumors that commonly occur in the head and neck, mediastinum and extremities. Pelvic schwannomas are very rare. Patients with pelvic schwannomas have different clinical presentations. We reported 2 cases of schwannomas found at the presacral area. The mass was found incidentally in one of the cases and the patient was completely asymptomatic. Abstract: Introduction: Schwannomas are benign tumors that arise from the Schwann cells of nerve fibers. They commonly occur in the head and neck, mediastinum and extremities. However, they are extremely rare to be found in the pelvis. Case presentation: We report two cases of pelvic presacral schwannomas found in our hospital. The first case is a 50 years old lady who was seen in the outpatient clinic complaining of pelvic heaviness. Investigations were done including Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) which showed a solid mass in the presacral area. Biopsy was taken, and results came back as schwannoma. The patient underwent exploratory laparotomy and total tumor resection. The second case is a 19 years old gentleman who was referred from a local hospital to our hospital for further evaluation of an asymptomatic left retroperitoneal pelvic mass. The mass was found incidentally after a Road Traffic Accident. The patient underwent exploratory laparotomy and total tumor resection. In the two cases, specimen histopathology report came back positive for schwannoma and patients were doing fine in the post-operative period with no signs of recurrence till this date. Conclusion: Due to the few cases in the literature, the diagnosis of presacral schwannoma is challenging. Some patients presented with vague symptoms like pelvic heaviness as seen with the patient in the first case, and some presented completely asymptomatic as seen with the patient in the second case. In symptomatic and asymptomatic cases, surgical excision is the mainstay of treatment of these tumors.